Colonizing, decolonizing, and globalizing Kolkata : from a colonial to a post-Marxist city - Sen, Siddhartha, 1957- (Asian cities (Amsterdam, Netherlands), 2017)
Colonising, Decolonising, and Globalising Kolkata' offers an extended analysis of the architecture of Kolkata from the earliest days of colonialism through independence and on into the twenty-first century, all set in the larger context of Indian cities and architecture. What Siddhartha Sen shows is the transformation of a colonial city into a Marxist one-and ongoing attempts to further transform it into a global city. Richly illustrated, the book carefully situates architecture, design, and urban planning within Kolkata's political economy and social milieu.